2014
DOI: 10.1007/s10120-014-0423-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of catumaxomab administered intra- and postoperatively as part of a multimodal approach in primarily resectable gastric cancer

Abstract: Background Postoperative relapse rate after gastrectomy and perioperative chemotherapy remain high in patients with advanced gastric cancer due to the spread of disseminated tumour cells in the peritoneal cavity. Perioperative administration of catumaxomab could potentially eliminate residual tumour cells after intended curative resection of the primary tumour. Methods This open-label, phase II study investigated the safety and efficacy of catumaxomab following neoadjuvant chemotherapy and subsequent surgery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Five of the nine patients also had stable or partial regression of disease, with a mean overall survival of 11.8 months, compared to a mean survival of 6 months in the EVOCAPE study by Sadeghi et al [ 91 , 95 ]. Catumaxomab has also been shown to have a tolerable toxicity profile in patients with resectable gastric cancer treated perioperatively [ 88 ]. Catumaxomab in combination with paracentesis can be effective in treating malignant ascites and improving the overall survival and quality of life of ovarian and gastric cancer patients [ 91 , 96 ].…”
Section: Catumaxomabmentioning
confidence: 99%
“…Five of the nine patients also had stable or partial regression of disease, with a mean overall survival of 11.8 months, compared to a mean survival of 6 months in the EVOCAPE study by Sadeghi et al [ 91 , 95 ]. Catumaxomab has also been shown to have a tolerable toxicity profile in patients with resectable gastric cancer treated perioperatively [ 88 ]. Catumaxomab in combination with paracentesis can be effective in treating malignant ascites and improving the overall survival and quality of life of ovarian and gastric cancer patients [ 91 , 96 ].…”
Section: Catumaxomabmentioning
confidence: 99%
“…In patients with malignant ascites from PC of gastric origin, it was found to significantly prolong OS from 44 to 71 d[ 45 ]. Bokemeyer et al[ 46 ] conducted a phase 2 study where patients underwent intra- and post-operative intraperitoneal catumaxomab administration after undergoing neoadjuvant chemotherapy and resection. These patients had four-year disease-free survival rates of 38% and four-year OS rates as high as 50%.…”
Section: Future Effortsmentioning
confidence: 99%
“…EpCAM has long been considered a potential target for antitumour therapy, and vaccination with EpCAM protein has been proposed (Mosolits et al , 2004). Furthermore, clinical trials of mAbs have ranged from testing the first murine IgG2a antibody, termed edrecolomab (Mosolits et al , 2004), to the EpCAM/CD3 bi-specific antibody MT110 (NCT00635596) and catumaxomab (Heiss et al , 2010; Goere et al , 2014; Bokemeyer et al , 2015), and ultimately to human engineered or fully human antibodies including ING-1 (Mosolits et al , 2004) and adecatumumab (MT201; Schmidt et al , 2012). Heiss et al (2010) found that catumaxomab provided a significant clinical benefit to GC patients with malignant ascites in a phase II/III trial.…”
Section: Clinical Targeted Therapymentioning
confidence: 99%
“…Heiss et al (2010) found that catumaxomab provided a significant clinical benefit to GC patients with malignant ascites in a phase II/III trial. Another study has also demonstrated the safety and efficacy of catumaxomab in patients with resectable GC when serving as a part of a combined modality therapy (Bokemeyer et al , 2015). Moreover, a phase II trial of the intraperitoneal infusion of catumaxomab to treat postoperative GC patients with resectable primary lesions and peritoneal carcinomatosis is currently underway (Goere et al , 2014).…”
Section: Clinical Targeted Therapymentioning
confidence: 99%